Patients' real-world experience with inflammatory bowel disease: A cross-sectional survey in tertiary care centres from the GETAID group. Issue 4 (April 2021) - Nachury, Maria; Bouhnik, Yoram; Serrero, Melanie; Filippi, Jerome; Roblin, Xavier; Kirchgesner, Julien; Bouguen, Guillaume; Franchimont, Denis; Savoye, Guillaume; Buisson, Anthony; Louis, Edouard; Nancey, Stephane; et al.
Abstract: Background: Patients' experience with healthcare professionals could influence their clinical outcomes. Aims: To assess inflammatory bowel disease (IBD) patients' experience with their disease, their treatment and their relationship with their physician. Methods: A one-week cross-sectional study was conducted in 42 IBD centres. 2011 consecutive outpatients with IBD completed an anonymous self-report questionnaire assessing their experience with and knowledge of IBD. Results: A quantitative assessment of the doctor-patient relationship revealed that patients' knowledge of IBD and IBD treatment ranged from 7.4 to 8.3 out of 10. In addition to IBD physicians, other sources of information about IBD and current treatment mainly included the internet (80% and 63%, respectively) and general practitioners (61% and 54%). Knowledge about education programmes (28%) was poor, resulting in a lack of willingness to further use these resources (25%). Concerns about IBD treatment were raised in 76% of patients, mostly related to the fear of adverse events (47%) and a lack of efficacy (33%). The need of alternative healthcare professionals was reported by 89% of the sample. Conclusion: In a large cohort of patients, we highlighted gaps in the management of patients with IBD regarding the need for higher-quality information and the implementation of alternative healthcare professionals.